Defining cinema - Lehman, Peter (Rutgers depth of field series, 1997)
Defining Cinema is the first book to bring together leading theorists and scholars to discuss the importance of film theory to cinema studies. Peter Lehman introduces the volume by explaining what constitutes film theory and outlining the major positions within the field by placing these five theorists and their work within a historical perspective. Andre Bazin and Siegfried Kracauer represent realist film theories, and Sergei Eisenstein represents a formalist position. Noel Burch and Christian Metz are contemporary theorists who have moved beyond the classical realist-formalist opposition. Burch's theory encompasses films and styles praised by both Bazin and Eisenstein, and Metz helped bring semiotics and psychoanalytic theory to prominence in the field.